Marine heatwaves and warm events in the Cape Peninsula upwelling cell, Southern Benguela - Petzer, Kirstin Robyn (Department of Oceanography, 2026)
Due to global warming, Marine Heatwaves (MHWs) are considered to be one of the emerging threats to marine ecosystems globally. MHWs are prolonged periods of extreme warm Sea Surface Temperature (SST) anomalies which can cause severe ecological impacts by decreasing biodiversity, negatively affecting cold water species and increasing ocean stratification. Using the Cape Point CSIR half-hourly in situ SST, CCI, REMSS, ERA5 wind time series, over 17-years the occurrence from January 2003 to March 2020, duration and maximum SST values as well as the influence of the wind on the formation and end on marine heatwaves and warm events (WEs) at a single location in the Cape Peninsula Cell, in the Southern Benguela, was examined. The MHW events were identified using Hobday et al. (2016), when the SST exceeds the climatological 90th percentile for at least five days. The WE events, defined similarly to a MHW but the SST must exceed the climatological 90th percentile for at least three days, are also studied due to the high variability of the Southern Benguela. In the half-hourly CSIR time series 14 MHWs and 21 WEs occurred over the 17 years. The average duration is between 7 to 8 days but the longest events occurred during periods of decreased upwelling but the highest maximum SSTs occur during the periods of upwelling dominance. The daily CSIR, CCI and REMSS time series all identified double the number of MHWs and WEs events than the half-hourly time series, raising the concern of applying the Hobday et al. (2016) definition to sub-daily time series and the ability of satellites to be used for MHW identification in the Southern Benguela close to the coast. The dominant wind at the formation of MHWs and WEs is a north-westerly wind, indicating the main driver of events at the CSIR Cape Point mooring is the movement of warm water masses to the mooring location. The dominant wind direction at the end of the MHWs and WEs is a south-easterly wind indicating that coastal upwelling limits the duration of warm water events at the Cape Point mooring. Marine heatwaves are expected to worsen globally with climate change by lasting longer with high temperature increases but the projected increase in southeasterly winds could further limit the duration of MHWs in the Southern Benguela upwelling system.